UWI launches single vitual university space (2013)
Presents item on the launch of the first SVUS pilot IN MSc in Development Studies offered by SALISES. Aims to deliver service via technologies such as video conferencing, web conferencing and web-based learning management systems.
Keywords: EDUCATIONAL PROJECTS